Islamic perspectives of reproductive and maternal health: what role can Nigerian Muslim religious leaders play in the prevention of maternal mortality? –With Particular Reference to Zamfara State NorthWest Nigeria - Mohammed Maiwada, Abdullahi; Mamat, Nik Mazlan; A. Rahman, Nor Azlina; Abdul Rahman, Suzanah; Mohammed Baba, Tukur (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
Reproductive and Maternal health are an important components of public health and medicine which are concerned with the complete state of physical, mental and social wellbeing in all matters regarding reproductive system and health of mother especially during pregnancy.It implies ensuring that all women receive the care they need to be safe and healthy throughout pregnancy, childbirth and beyond. However, according to World Health Organization, millions of women all over the world do not have access to good quality health services during pregnancy and childbirth resulting in mortalities. Islam is a complete way of life. The Qur’an and Hadith consider pregnancy and child bearing as signs among other signs of the divine existence of Allah.The importance of maternal and reproductive is thus not unexplained in the Islamic perspectives. The study look at what role Muslim religious leaders can play in the prevention of maternal deaths and morbidities in developing countries. A qualitative study was conducted through in-depth interviews and focus groups discussion with a purposive sample of some Muslim religious leaders from Gusau local government area of Zamfara state northwest Nigeria in order to elicit information about the Islamic perspectives of reproductive and maternal health and the roles they can play in the prevention of maternal deaths among the Muslim communities. Muslim Religious leaders have a crucial role and contribution for the attainment and maintenance of good heath of women and children among Muslim communities through public enlightenment in the context of ‘ilm’, providing guidance through ‘Fatwah’ and community mobilization in the spirit brotherhood ‘ukhuwah’.Islam does not accept the “preventable death of a woman” due to childbirth or pregnancy. Thus, Islam encourages attendance of antenatal care visits and health care seeking.